Evaluating the removal of pigs from a group and subsequent floor space allowance on the growth performance of heavy-weight finishing pigs - Flohr, Joshua R.; Tokach, Michael D.; DeRouchey, Joel M.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S. (My University, 2017)
A total of 1,092 finishing pigs (initially 36.3 kg) were used in a 117-d study to evaluate the impact of initial floor space allowance and removal strategy on the growth of pigs up to 140 kg BW. There were 4 experimental treatments with 14 pens per treatment. The first treatment provided 0.91 m(2) per pig (15 pigs/pen). The other 3 treatments initially provided 0.65 m(2) per pig (21 pigs/pen) with 3 different removal strategies. The second treatment (2:2:2) removed the 2 heaviest pigs from pens on d 64, 76, and 95 when floor space allowance was predicted to be limiting. Treatment 3 (2:4) removed the 2 heaviest pigs on d 76 and the 4 heaviest pigs on d 105. Treatment 4 (6) removed the heaviest 6 pigs on d 105. All pigs remaining in pens after removals were fed to d 117. Overall (d 0 to 117), pigs initially provided 0.91 m(2) of floor space had increased (P < 0.05) ADG compared to pigs in pens on the 2: 4 or 6 removal strategy, but ADG was not different compared with pigs on the 2:2:2 removal strategy. Total BW gain per pen was greater (P < 0.05) for pens initially stocked at 0.65 m(2) compared to pens initially stocked at 0.91 m(2). Feed usage per pen was less (P < 0.05) for pens initially stocked at 0.91 m(2) compared to pens initially providing 0.65 m(2) of floor space and on removal strategies; however, feed usage per pig was greater (P < 0.05) for pigs initially stocked at 0.91 m(2) compared to pigs initially stocked at 0.65 m(2) and on removal strategies. Feed usage, on a pig or pen basis, was less (P < 0.05) for pigs on the 2: 2: 2 removal strategy compared to pigs on the 2:4 or the 6 removal strategy. Income over feed and facility cost (IOFFC) was less (P < 0.05) for pigs initially provided 0.91 m(2) compared to pigs initially provided 0.65 m(2) and on removal strategies. Also, IOFFC was less (P < 0.05) for pigs on the 2:2:2 compared to the 2:4 and 6 removal strategies. In conclusion, increasing the floor space allowance or the time points at which pigs are removed from the pen improved the growth of pigs remaining in the pen; however, IOFFC may be reduced because fewer pigs are marketed from each pen (pigs stocked at 0.91 m(2) throughout the study) or from reducing total weight produced (2:2:2 removal strategy).
Citation: Flohr, J. R., Tokach, M. D., DeRouchey, J. M., Woodworth, J. C., Goodband, R. D., & Dritz, S. S. (2016). Evaluating the removal of pigs from a group and subsequent floor space allowance on the growth performance of heavy-weight finishing pigs. Journal of Animal Science, 94(10), 4388-4400. doi:10.2527/jas2016-0407
Keywords: Finishing Pig; Floor Space; Late Finishing; Removals; Swine; Agriculture